Monetarism, open-economy policies and the ideological crisis - Raúl Prebisch (CEPAL Review, 1982)
In his recent articles, and especially in his latest book (Capitalismo periférico. Crisis y transformación, Fondo de Cultura Económica, Mexico City, 1981), the author pays special attention to the role played by monetary mechanisms in peripheral capitalism and to the meaning and limits of their use by the monetary authority.